Glyphosate sensing in aqueous solutions by fluorescent zinc(ii) complexes of [9]aneN3-based receptors. Issue 22 (25th May 2022) - Garau, Alessandra; Picci, Giacomo; Bencini, Andrea; Caltagirone, Claudia; Conti, Luca; Lippolis, Vito; Paoli, Paola; Romano, Giammarco Maria; Rossi, Patrizia; Scorciapino, Mariano Andrea
Abstract : Binding ability of Zn(ii ) complexes of [9]aneN3 -based receptors for selective recognition of glyphosate in aqueous media. Abstract : Herein we describe the binding abilities of Zn(ii ) complexes of [12]aneN4 - (L1 ) and [9]aneN3 -based receptors (L2, L3 ) towards the herbicides N -(phosphonomethyl)glycine (glyphosate, H3 PMG) and 2-amino-4-[hydroxy(methyl)phosphoryl]butanoic acid (glufosinate, H2 GLU), and also aminomethylphosphonic acid (H2 AMPA), the main metabolite of H3 PMG, and phosphate. All ligands form stable Zn(ii ) complexes, whose coordination geometries allow a possible interaction of the metal center with exogenous anionic substrates. Potentiometric studies evidenced the marked coordination ability of the L2 /Zn(ii ) system for the analytes considered, with a preferential binding affinity for H3 PMG over the other substrates, in a wide range of pH values. 1 H and 31 P NMR experiments supported the effective coordination of such substrates by the Zn(ii ) complex of L2, while fluorescence titrations and a test strip experiment were performed to evaluate whether the H3 PMG recognition processes could be detected by fluorescence signaling.